Bending of Sheet Metal (st37) Using 90 Degree to Estimate Blank Dimensions (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Several factors must be considered whendesigning parts that are being made by bending. Theprimary factor is minimum radius and angle of bending thatcan be bent successfully without metal cracking. Lowcarbon steel metal (st37), manufactured by Libyan Iron andsteel Company, was used in this study. Various bendingprocesses by Vee die for different radii and calculatethickness were conducted and bending zones were tested tofind the mean radius and calculate the bending allowance.These calculations depend upon the inner bend radius andthickness of the sheet metal. The thickness was reduced andthe neutral axis were moved up in the direction ofcompression side. Form the values of reduction in thicknessand different radii of bending a chart was drawn. Anotherchart was drawn to minimums the process of trial and errorfor estimating the blank length of the bending sheet metal.Form these charts, the initial blank sizes can be determined,so that products can bend without loss and crack in thematerial. As a result time and material can be saved. Theresults of the present study can have practical applicationsfor this material (st37) which is in common use by theLibyan industry.